Income level is associated with differences in primary and secondary stroke prevention in China - Huiming Ren; Junrong Ma; Xu Guo; Ruijie Zhang; Liyuan Pu; Tian Zhao; Fangfang Zeng; Chang Shu; Liyuan Han; Yunzhi Wang; Qiang Li; Xiaojie Wang (Archives of Medical Science)
Introduction The aim of this study was to assess differences in the effects of income level on the primary and secondary prevention of stroke in the Chinese population.